Clinical Features and Outcomes of the Association of Co-Infections in Children with Laboratory-Confirmed Influenza during the 2022–2023 Season: A Romanian Perspective - Mădălina-Maria Merișescu; Monica Luminița Luminos; Carmen Pavelescu; Gheorghiţă Jugulete (Viruses, 2023)
The 2022–2023 influenza season in Romania was characterized by high pediatric hospitalization rates, predominated due to influenza A subtypes (H1N1) pdm09 and H3N2. The lowered population immunity to influenza after the SARS-CoV-2 pandemic and the subsequent stoppage of influenza circulation, particularly in children who had limited pre-pandemic exposures, influenced hospitalization among immunosuppressed children and patients with concurrent medical conditions who are at an increased risk for developing severe forms of influenza. This study focused on the characteristics of influenza issues among pediatric patients, as well as the relationship between different influenza virus types/subtypes and viral and bacterial co-infections, as well as illness severity in the 2022–2023 season after the SARS-CoV-2 pandemic. We conducted a retrospective clinical analysis on 301 cases of influenza in pediatric inpatients (age ≤ 18 years) who were hospitalized at the National Institute of Infectious Diseases “Prof. Dr. Matei Balș” IX Pediatric Infectious Diseases Clinical Section between October 2022 and February 2023. The study group’s median age was 4.7 years, and the 1–4 year age group had the highest representation (57.8%). Moderate clinical forms were found in 61.7% of cases, whereas severe versions represented 18.2% of cases. Most of the complications were respiratory (acute interstitial pneumonia, 76.1%), hematological (72.1%, represented by intra-infectious and deficiency anemia, leukopenia, and thrombocytopenia), and 33.6% were digestive, such as diarrheal disease, liver cytolysis syndrome, and the acute dehydration syndrome associated with an electrolyte imbalance (71.4%). Severe complications were associated with a risk of unfavorable evolution: acute respiratory failure and neurological complications (convulsions, encephalitis). No deaths were reported. We noticed that the flu season of 2022–2023 was characterized by the association of co-infections (viral, bacterial, fungal, and parasitic), which evolved more severely, with prolonged hospitalization and more complications (p < 0.05), and the time of use of oxygen therapy was statistically significant (p < 0.05); the number of influenza vaccinations in this group was zero. In conclusion, co-infections with respiratory viruses increase the disease severity of the pediatric population to influenza, especially among young children who are more vulnerable to developing a serious illness. We recommend that all people above the age of six months should receive vaccinations against influenza to prevent the illness and its severe complications.